Framework for early warning of animal health threats - Food and Agriculture Organization of the United Nations (Food and Agriculture Organization of the United Nations, 2025)
Increasing the number of countries that adopt and implement national disaster risk reduction strategies is a key indicator of the Priority Programme Area One Health (OH PPA). This contributes to the better production goal of the FAO Strategic Framework 2022–2031, which seeks “transformation to more efficient, inclusive, resilient and sustainable agrifood systems for better production, better nutrition, a better environment, and a better life, leaving no one behind.” Effective early warning systems (EWS) are a critical component of reducing risk. This framework outlines the technical objectives and the structural and institutional setup for the operationalization and management of early warning systems against infectious animal diseases, under a systems approach. This approach considers the overall strengthening of animal health surveillance systems and the capacity to implement risk-based strategies and respond to detected signals. The framework is not intended to add the burden of creating new systems but to guide countries in strengthening components already in place, with the specific aim of improving the efficacy of existing systems to detect and respond to hazards as early and reliably as possible. The scope of this framework is not limited to the early detection of new and emerging threats, or the identification of alerts with emergent potential. It encompasses all information collected through risk monitoring and disease surveillance, as well as the timely collation of that information to inform prevention, detection and control measures. Inspired by the Sendai Framework for Disaster Risk Reduction 2015–2030 and related resources, this framework considers an early warning system to be composed of four main components.